The effects of excess calcium on the handling and mechanical properties of hydrothermal derived calcium phosphate bone cement - Razali N.N.; Sukardi M.A.; Sopyan I.; Mel M.; Salleh H.M.; Rahman M.M. (Institute of Physics Publishing, 2023)
Bone; Bone cement; Calcium phosphate; Compressive strength; Hydroxyapatite; Lime; Manufacture; Mechanical properties; Ammonium dihydrogen phosphate; Calcium phosphate bone cement; Calcium phosphate cement; Distilled water; Hydrothermal methods; Hydroxyapatite powder; Morphological properties; Synthesized powder; Calcium